Psikoterapi Sabar sebagai Pendekatan Psikologis dalam Membangun Ketahanan Mental di Era Modern - Rahma Suryani; Khairunnas Rajab (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Mental health has become a significant issue in the modern era due to increasing life pressures, work demands, and rapid social changes. These conditions contribute to various psychological problems such as stress, anxiety, and depression, highlighting the need for comprehensive and adaptive intervention approaches. This study aims to examine the concept and development of patience-based psychotherapy as a psychological approach to enhancing mental resilience. The research employs a qualitative approach using a literature review method by analyzing relevant scientific sources, including journal articles, books, and academic publications. The findings indicate that patience is a psychological construct encompassing emotional regulation, resilience in facing difficulties, and the ability to accept reality adaptively. The conceptual model of patience-based psychotherapy consists of several key components, namely self-awareness, acceptance, emotional control, resilience, and meaning-making. Through systematic intervention stages, this approach helps individuals manage life stressors more calmly, rationally, and adaptively. Empirical evidence also shows that patience is positively associated with psychological well-being, happiness, and effective coping abilities. Therefore, patience-based psychotherapy has strong potential as a holistic and relevant psychological intervention to enhance mental resilience in the modern era.